2007
DOI: 10.1090/s0002-9939-07-08868-5
|View full text |Cite
|
Sign up to set email alerts
|

The Weil-Petersson geometry on the thick part of the moduli space of Riemann surfaces

Abstract: Abstract. In the thick part of the moduli space of Riemann surfaces, we show that the sectional curvature of the Weil-Petersson metric is bounded independently of the genus of the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Proof. The proof follows closely the proofs to obtain lower and upper bounds given in [16,4]. For completeness, we repeat it here.…”
Section: Lemma 31 Let G Be the Positive Self-adjoint Operator Onmentioning
confidence: 70%
See 3 more Smart Citations
“…Proof. The proof follows closely the proofs to obtain lower and upper bounds given in [16,4]. For completeness, we repeat it here.…”
Section: Lemma 31 Let G Be the Positive Self-adjoint Operator Onmentioning
confidence: 70%
“…Therefore, attention must be shifted to find lower bounds of the sectional curvature on compact subsets of the moduli space M g . This problem was studied by Huang in [4]. To describe his result in more detail, we need to introduce some notation first.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The curvature of the Weil-Petersson metric is not bounded negatively from above, as was first shown by Huang [27] who found that the curvature goes to 0 in certain directions when approaching the boundary of moduli space. This issue has been further investigated in [29,74]. Also, in [56] it was shown that the Weil-Petersson metric is not Gromov hyperbolic.…”
Section: 22mentioning
confidence: 99%